Merkel 세포암 - 권기환(Ki Hwan Kwon); 심효섭(Hyo Sup Shim); 김봉수(Bong Soo Kim); 박세호(Se Ho Park); 김태승(Tei Seung Kim); 신규호(Kyoo Ho Shin); 김충배(Choong Bai Kim); 김순일(Soon Il Kim); 김유선(Yu Seun Kim); 박기일(Kiil Park) (Annals of surgical treatment and research, 2002)
KCI Citation Count: 0